Immunomodulatory Effect of Ethanol Extract of Pirdot Leaf (Saurauia vulcani Korth ) on CD4+ and IL-2 Hepatic Profile in Tyfoid Fever - Haslinda; Rina Amelia; Muhammad Ichwan; Dwirita Anggraini; Yunita Sari Pane (Talenta Publisher, 2023)
Typhoid fever is an acute febrile disease caused by Salmonella typhi bacteria that is obtained orally either through food or from drinks.Many immunological activities that occur due to salmonella infection so that immunomodulators are needed to speed up the healing of one of them by using pirdot leaves. Pirdot leaves are widely distributed in Indonesia, especially in the Lake Toba area of North Sumatra.This plant has many bioactive components, one of which is flavonoids.The flavonoid component of pirdot Leaf has been widely studied and is believed to improve the immune system because it is able to increase the production of IL-2 which is involved in the activation and proliferation of lymphocyte cells and can increase T CD4 cells. T CD4+ it self is a signal transduction marker in the mechanism of typhoid fever that can activate Antigen Precenting Cell (APC) to provide resistance to foreign substances.